Utilizing Regulatory T Cells Against Rheumatoid Arthritis - Haque, Mohammad (Frontiers Media S.A., 2014)
Regulatory T (Treg) cells are essential for normal immune surveillance systems, and their dysfunction leads to development of diseases, such as autoimmune disorders. CD4(+)CD25(+) Treg cells are well-known suppressive cells, which express the transcription factor Foxp3, are indispensable for the maintenance of immune self-tolerance and homeostasis by suppressing aberrant or excessive immune response. Other Foxp3(−) Treg cells include Tr1, Th3, CD8(+)CD28(−/−), and Qa1-restricted T cells; however, the contribution of these Treg cells to self-tolerance, immune homeostasis as well as preventing autoimmunity is not well defined. Here, we discuss the phenotypes and function of Foxp3(+) Treg cells and the potential use of such Treg cells against rheumatoid arthritis (RA). Of note, even though most expanded populations of Foxp3(+) Treg cells exhibit suppressive activity, tissue-associated or antigen-specific Treg cells appear superior in suppressing local autoimmune disorders such as RA. In addition, utilizing tissue-associated Foxp3(+) Treg cells from stem cells may stable Foxp3 expression and avoid induction of a potentially detrimental systemic immunosuppression.